Towards High Extinction Ratio in Silicon Thermo-Optic Switches—Unravelling Complexity of Fabrication Variation - Rui Zhu; Xin Zhou; Nan Yang; Lemeng Leng; Wei Jiang (IEEE Photonics Journal)
$2× 2$ Mach–Zehnder thermo-optic switches on silicon are found to exhibit huge difference of extinction ratios between the bar and cross port, with the bar port lower by up to 20 dB. Device physics analysis shows that this can be explained by synchronous variation of the splitting ratios of the two directional couplers in a switch. Furthermore, for the two waveguides in each coupler, small differential variation of their dimensions can create much larger effects than substantial synchronous variation. This illustrates the complexity of fabrication variation in active silicon photonic devices, and an approach to unraveling the complexity through separating the device level and structure level.